Music in the galant style - Gjerdingen, Robert O.; Oxford University Press (New York : Oxford University Press, 2007)
"Music in the Galant Style is the first book to examine the cognitive development of elite eighteenth-century musicians. Hundreds of musical examples from more than seventy composers illustrate the standard patterns that formed a core vocabulary for aspiring galant musicians. These patterns - schemata - provided an aural medium of exchange between a patron and his or her musicians. By providing a known context for most phrases and cadences, the galant schemata helped to foster a music culture in which the patron's public display of taste and discernment was a central feature." "In documenting the link between training in partimenti and the student musician's cognitive development of a repertory of preferred schemata, Music in the Galant Style pioneers a new approach to this centuries-old, but still living music tradition. By analogy to "historically informed" performance practice, the book suggests a new type of historically and cognitively informed music analysis. It offers a new set of tools to explore the very particular sense of musical etiquette that pervaded contemporary discourse on eighteenth-century music and its musicians." "The book will help students, scholars, performers, and all lovers of eighteenth-century music to develop a deeper understanding of eighteenth-century music and to broaden their view of the repertoire."--BOOK JACKET.
-- The romanesca -- The prinner -- The fonte -- A Minuet by Giovanni Battista Somis -- The do-re-mi -- The monte -- A Theme and variations by Carl Ditters von Dittersdorf -- The meyer -- A Theme and variations by Joseph Haydn -- Clasulae -- An Andante by Christoph Willibald Gluck -- The quiescenza -- The ponte -- A Grave sostenuto by Baldassare Galuppi -- The fenaroli -- An Allegro by Carl Ditters von Dittersdorf -- The sol-fa-mi -- An Andante by Johann Christian Bach -- The indugio -- A Cantabile by Simon Leduc -- A Larghetto by Leonardo Leo -- An Andantino by Baldassre Galuppi -- An Andantino affettuoso by Niccolo Jommelli -- The child Mozart -- An Allegro by Wolfgang Amadeus Mozart -- Il filo : a Poco adagio by Joseph Haydn -- A model Adagio by Johann Joachim Quantz -- A model Allegro by Francesco Galeazzi -- Summary and cadenza.
Includes index.
Keywords: Music -- Europe -- 18th century -- History and criticism; Style, Musical; Musical analysis